2005
DOI: 10.1097/00000542-200507000-00019
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Sequential Epidural Bolus Technique and Continuous Epidural Infusion

Abstract: The SEB technique with ropivacaine provides superior epidural block compared with an identical hourly dose administered as a continuous infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 11 publications
0
24
1
Order By: Relevance
“…This new method reduced the amount of medication and provided better pain relief than a continuous epidural infusion. [22][23][24] In patients who received postoperative thoracic epidural analgesia, Ueda et al 21 found that programmed epidural bolus administration of local anesthetic resulted in more anesthetized spinal segments compared with a continuous infusion. Experimentally, the use of intermittent bolus doses resulted in a wider spread of solution when compared with a continuous infusion, despite a similar infusion rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This new method reduced the amount of medication and provided better pain relief than a continuous epidural infusion. [22][23][24] In patients who received postoperative thoracic epidural analgesia, Ueda et al 21 found that programmed epidural bolus administration of local anesthetic resulted in more anesthetized spinal segments compared with a continuous infusion. Experimentally, the use of intermittent bolus doses resulted in a wider spread of solution when compared with a continuous infusion, despite a similar infusion rate.…”
Section: Discussionmentioning
confidence: 99%
“…3,14 -20 A new dosing regimen of automated bolus administration has been described for epidural analgesia with excellent results. [21][22][23][24] However, no information is currently available using this dosing regimen for continuous peripheral nerve blocks. The objective of this prospective, randomized, double-blind study was to compare two different dosing regimens: a conventional continuous infusion of local anesthetic with automated bolus doses and their impact on pain relief and IV analgesic requirements in patients undergoing continuous popliteal sciatic nerve blockade for postoperative analgesia.…”
mentioning
confidence: 99%
“…Programmed intermittent bolus infusion (PIBI) and continuous infusion (CI) are commonly used methods of continuous nerve block for postoperative patient-controlled analgesia (PCA). It has been demonstrated that sequential epidural boluses improve the quality of sensory blockade as compared with a continuous epidural block 6. Similarly, Taboada et al found that local anesthetic administered during a continuous popliteal block as a programmed bolus provided similar pain relief, and reduced the need for PCA, as well as demonstrating a decrease in overall consumption of local anesthetic 7.…”
Section: Introductionmentioning
confidence: 98%
“…Yokoyama et al 8 and Ueda et al 9 However, the phenomenon may also be considered inversely: epidural continuous infusion without an initial dose may spread the requisite extent of F i g . 1 B a r g r a p h a n d b o x p l o t o f t h e f r e q u e n c y o f f l u r b i p r o f e n a x e t i l u s e .…”
Section: Discussionmentioning
confidence: 99%